Environmental dispute resolution in Indonesia - Nicholson, David (Leiden - Boston Brill, 2010)
In the last two decades, Indonesia has seen a dramatic proliferation of environmental disputes in a variety of sectors, triggered by intensified deforestation and large scale mining operations in the resource rich outer islands, together with rapid industrialisation in the densely populated inner island of Java. Whilst the emergence of environmental disputes has sometimes attracted political repression, attempts have also been made in recent times to explore more functional approaches to their resolution. The Environmental Management Act of 1997 created a legal framework for the resolution of environmental disputes through both litigation and mediation. This book is the first attempt to analyse the implementation of this framework in detail and to assess the effectiveness of litigation and mediation in resolving environmental disputes in Indonesia. It includes a detailed overview of the environmental legal framework and its interpretation by Indonesian courts in landmark court cases. The book features a number of detailed case studies of both environmental litigation and mediation and considers the legal and non-legal factors that have influenced the success of these approaches to resolving environmental disputes. David Nicholson graduated in Law (Hons) and Asian Studies from Murdoch University in 1995 and was admitted to legal practice in Western Australia in 1997. He subsequently undertook doctoral research on environmental dispute resolution in Indonesia as part of the Indonesia Netherlands Study of Environmental Law and Administration (INSELA) project, based at the Van Vollenhoven Institute at Leiden University, and was awarded a doctorate in law in 2005. Dr Nicholson has since returned to legal practice in Western Australia, specializing in environmental planning and local government law.
English
Keywords: Society & social sciences; dispute settlement; indonesie; onderzoek; case studies; indonesia; district rechtbank; milieuwetgeving; environmental law; trials; milieubescherming; environmental protection; rechtszaak; district courts; geschilovereenkomst; Lawsuit; Mediation; Semarang; The Indonesian Forum for Environment; Waste management